Seasonal incidence and population dynamics of castor pests and their natural enemies in Tamil Nadu: Seasonal incidence and population dynamics of castor pests and their natural enemies in Tamil Nadu - B GEETHA; M SENTHIL KUMAR; M DEIVAMANI; S R VENKATACHALAM (Journal of Oilseeds Research, 2020)
Seasonal occurrence of insect pests and natural enemies on castor recorded consecutively for four years (2015-19 to 2018-19) showed that the sucking pests incidence was higher compared to defoliators and capsule borer. The peak incidence of leafhopper started from November to January in all the years with the peak population ranging from 24.8 to 84.5 leafhoppers/3 leaves/plant. Thrips population peaked during November and highest population of 432.8 thrips/spike was recorded during 2016-17. Whitefly population was recorded during December to January with peak population of 224.3/plant noticed in 2016-17. Defoliator population was recorded from October to November and the parasitisation of semilooper by Snellenius maculipennis was up to 66.6 per cent.